STUDENTS’ INFERENTIAL COMPREHENSION AND READING COMPREHENSION - Anne Valentine; Ida Rosmalina; Rita Hayati (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2015)
Abstract: The study was conducted to find out whether or not there was any significant correlation between inferential comprehension and reading comprehension of the students of English Education Study Program FKIP Sriwijaya University Indralaya, whether or not there is a contribution of inferential comprehension to the reading comprehension, whether or not there is any significant difference between male and female students and whether or not there is any significant difference among students of different semesters in terms of their inferential comprehension and their reading comprehension. The researcher used population sampling in which the total number of the students was 126 students. It consisted of 18 male students and 108 female students. To collect the data, the researcher used 2 kinds of tests, namely inferential comprehension test and reading comprehension test. The results of the tests were analyzed by using the Pearson Product Moment Coefficient Correlation through Statistical Package for Social Science (SPSS) 21.0, Multiple Linear Regression Analysis, t-Test, and ANOVA. The results showed that the correlation between inferential comprehension and reading comprehension was 0.627 in which inferential comprehension contributed 39.4% to the reading comprehension. It was also found that there was a significant difference between male and female students and also a significant difference among students of different semesters in terms of inferential comprehension and reading comprehension. Based on the findings, it could be concluded that there was a significant correlation between inferential comprehension and reading comprehension. Key words: inferential comprehension, reading comprehension, English Education Studi Program students